SUBSURFACE SEISMIC VELOCITY IMAGING IN TANGERANG AND SURROUNDING AREA BY USING HVSR METHOD - Fahrurrozi, Zakki
The city of Tangerang and its surroundings is a lowland which is dominated by loose deposits in the form of clay, gravel sand, and tuff rock deposits. The Tangerang area and its surrounding areas have the potential to experience earthquakes because they are close to active faults such as the Baribis and Cimandiri faults. Earthquakes originating from active fault movements generally have the potential to become a major disaster, especially faults that are close to settlements and other areas of human activity. The geophysical method commonly used to extract the dynamic properties of the ground surface is the horizontal/vertical component spectral ratio (HVSR) technique which requires recording data from a three-component seismometer. This method is based on calculating the spectral ratio between the vertical and horizontal components of the recorded data. Microtremor data processing using the HVSR method is a method that can describe subsurface conditions as well as measure the physical properties of seismicity. The microtremor data processed in this study is the microtremor power in the Tangerang area and its surroundings. This study intends to describe the subsurface conditions both lithology and subsurface structures using the HVSR method. Based on the processing results, the dominant frequency values are varied from 3.01 to 19.68 Hz. Low frequency values are found in the western part at several points of the study area and towards the east, relatively higher dominant frequency values are seen. The amplification value in the Tangerang area has a value range of 0.54 to 5.04. Areas that are dominated by small dominant frequency values describe a thick layer of sediment in that area. The dominant high amplification value is in the eastern part of the study area, while the low amplification value is in the western part of the study area. High amplification values tend to have large resonances. The inversion of the HVSR curve produces a distribution of subsurface shear wave velocity (Vs) values in the Tangerang area and its surroundings with a range of 84.54 m/s to 3100 m/s. Based on the distribution of Vs values, it is obtained that there are relatively low values in the western part of the Cikopa area and its surroundings